Frequency Effects with Visual Words and Syllables in a Dyslexic Reader - Prisca Stenneken; Markus Conrad; Florian Hutzler; Mario Braun; Arthur M. Jacobs (Behavioural Neurology, 2005)
The present study investigated the nature of the inhibitory syllable frequency effect, recently reported for normal readers, in a German-speaking dyslexic patient. The reading impairment was characterized as a severe deficit in naming single letters or words in the presence of spared lexical processing of visual word forms. Three visual lexical decision experiments were conducted with the dyslexic patient, an unimpaired control person matched to the patient and a control group: Experiment 1 manipulated the frequency of words and word-initial syllables and demonstrated systematic effects of both factors in normal readers and in the dyslexic patient. The syllable frequency effect was replicated in a second experiment with a more strictly controlled stimulus set. Experiment 3 confirmed the patient’s deficit in activating phonological forms from written words by demonstrating that a pseudohomophone effect as observed in the unimpaired control participants was absent in the dyslexic patient.